Mengkaji Konflik Kepentingan Antara Taksi Online Dan Taksi Bandara El Tari Kupang - yohanes ethelbert; Beatriks Tri Putri Pining; Indriyati Indriyati; Kristianus Simon H. Molan (STISIPOL Raja Haji, 2025)
The conflict of interest that occurs between online taxis and taxis of El Tari Kupang airport is one example of business competition in the field of transportation. This is an important issue that requires effective handling from policy makers. The purpose of this study is to analyze and identify conflicts between two different types of transportation services using the functional theory of conflict initiated by Lewis A. Coser using indicators of social change and adjustment, social stability, encouraging awareness and group identity, and problem solving and negotiation. The research method used in this research is descriptive qualitative conducted with in-depth interviews, observation and documentation data collection. Based on the results of the research, the handling of conflicts that occur between online taxis and taxis at El Tari Kupang airport has not been carried out effectively, the regulations made have not provided full answers to consumer needs, and regulations related to limiting the operational zone of online taxis at the airport have not been fully accepted by the community both from the users of online transportation services and as the business actors of onine taxis and are considered monopolistic. In relation to the above research results, this study provides recommendations for policy makers to consider the needs of the three targets of this policy such as airport taxis, online taxis and the public as users of transportation services.